Предмет: Алгебра, автор: jiocb1069

Решить два уравнения:
(x-4)(x-6)-(x-2)(x+2)=-2

(x-5)(x+8)-(x-7)(x+7)=3

Ответы

Автор ответа: nafanya2014
0
1) (x-4)(x-6)-(x-2)(x+2)=-2,
     (х²-4х-6х+24)-(х²-4)=-2,
       х²-10х+24-х²+4+2=0,
       -10х=-30
        х=(-30):(-10)
        х=3  
2) (x-5)(x+8)-(x-7)(x+7)=3
,
      х²-5х+8х-40 - (х²-49)=3,
     х²-5х+8х-40 - х²+49-3=0,
         3х+6=0
         3х=-6
         х=-2
Похожие вопросы
Предмет: Алгебра, автор: mariarts092
Предмет: Физика, автор: macarovasvetla